THE INFLUENCE OF TAX AWARENESS TOWARD TAX COMPLIANCE OF ENTREPRENEURIAL TAXPAYERS AND CELENGAN PADJEG PROGRAM AS A MODERATING VARIABLE: A Case Study At The Pratama Tax Office Of Wonosari Town - Suyanto Suyanto; Endah Trisnawati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The objectives of this research are to test the tax awareness in relation to the tax compliance and to examine Celengan Padjeg Program which acts as a moderating variable to build a relationship between the tax awareness and the tax compliance. This research was conducted using Convenience sampling consisted of 98 respondents from individual taxpayers in Wonosari, Yogyakarta, Indonesia. The sample was fundamentally based on 95 questionnaires. The data analysis method of this research was a multiple regression analysis and test interactions. The analysis results showed that the tax awareness affected the tax compliance with a significance level of 0,000 (0,05). The Celengan Padjeg Program influenced the relationship between the tax awareness and the tax compliance significantly and it moderated the relationship between two variables.